2021
DOI: 10.21203/rs.3.rs-849739/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating the Effect of Climate Internal Variability and Source of Uncertainty in Climate-Hydrological Projections in a Representative Watershed of Northeastern China

Abstract: The decomposition and quantification of uncertainty sources in ensembles of climate-hydrological simulation chains is a key issue in climate impact researches. The mainly objectives of this study partitioning climate internal variability (CIV) and uncertainty sources in the climate-hydrological projections simulation process, the climate simulation process formed by six downscaled GCMs under two emission scenarios called GCMs-ES simulation chain, the hydrological simulation process add one calibrate Soil and W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…found that flood frequency and wintertime runoff in Europe are mostly influenced by choice of GCM, although they quantified natural climate variability using a limited number of GCM integrations with different initial conditions. found that natural variability highly influences low flows in snow-dominated catchments in the French Alps, and Cai et al (2021) found that natural variability is a dominant driver of rainy season runoff in Northeastern China. quantified natural variability using a block bootstrap on the historical record and found it to have the largest impact on the variance of large floods, as compared to GCM structure, emission scenario, land use change scenario, and hydrologic model parameter uncertainty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that flood frequency and wintertime runoff in Europe are mostly influenced by choice of GCM, although they quantified natural climate variability using a limited number of GCM integrations with different initial conditions. found that natural variability highly influences low flows in snow-dominated catchments in the French Alps, and Cai et al (2021) found that natural variability is a dominant driver of rainy season runoff in Northeastern China. quantified natural variability using a block bootstrap on the historical record and found it to have the largest impact on the variance of large floods, as compared to GCM structure, emission scenario, land use change scenario, and hydrologic model parameter uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…These studies primarily attribute variability in projected global and regional temperature and precipitation to climate change scenario uncertainty, global climate change model (GCM) uncertainty, and natural variability.Lehner et al (2020) shows that scenario and model uncertainty are the dominant drivers of global decadal mean annual temperature and precipitation, but that natural variability dominates projections of regional temperatures (in Southern Europe) and precipitation (in the U.S. Pacific Northwest and Sahel region), particularly at shorter (and more decision-relevant) time scales. Fewer studies have explicitly considered the role of natural climate variability when partitioning variance in projections of hydrologic and water systems variablesCai et al, 2021). found that flood frequency and wintertime runoff in Europe are mostly influenced by choice of GCM, although they quantified natural climate variability using a limited number of GCM integrations with different initial conditions.…”
mentioning
confidence: 99%
“…Lehner and Deser (2023) similarly demonstrates how natural variability becomes the increasingly dominant driver of variability in winter mean air temperature projections at smaller spatial scales. Fewer studies have explicitly considered the role of natural climate variability when partitioning variance in projections of hydrologic and water systems variables (Cai et al., 2021; I.‐W. Jung et al., 2011; Kay et al., 2009; Schlef et al., 2018; Vidal et al., 2015; Whateley & Brown, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Lehner and Deser (2023) similarly demonstrates how natural variability becomes the increasingly dominant driver of variability in winter mean air temperature projections at smaller spatial scales. Fewer studies have explicitly considered the role of natural climate variability when partitioning variance in projections of hydrologic and water systems variables (Cai et al, 2021;I.-W. Jung et al, 2011;Kay et al, 2009;Schlef et al, 2018;Vidal et al, 2015;Whateley & Brown, 2016). Kay et al (2009) found that flood frequency and wintertime runoff in Europe are mostly influenced by choice of GCM, although they quantified natural climate variability using a limited number of GCM integrations with different initial conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation